Alternatives to high-risk securities fraud control: proposing structural transformation in an age of financial expansionism and unsustainable global capital - Barak, Gregg (Crime, law and social change, 2016)
This article is not about controlling high-risk securities frauds through improved identification and enhanced enforcement of existing (or new) administrative, civil, and/or criminal laws. Instead, it is about demonstrating the futility of these strategies and revealing the structural necessities for developing other strategies of social control. It proceeds by locating financial global capital within the world economy as a means of familiarizing discussions of crime control with the laws of capitalist development. To advance the argument for alternative policies, it first describes the contradictory forces of free-market capitalism as well as the failures of securities law to deter Wall Street like financial frauds, and then it appraises the inefficacies and non-controls of state-legal interventions into high-stakes financial frauds. Ultimately, within the framework of building a globally sustainable ecosystem, a number of policy prescriptions are presented. Collectively, these policies revolve around the redistributions of social, political, and economic power as a plan for avoiding future securities trading catastrophes caused primarily by the concentrations of global capital.